Relationship between the exit profile and the competences of the curriculum courses of the secondary education professional school of Universidad Nacional del Altiplano Puno (Revista Innova Educación, 2020)
The objective of the research was to determine the degree of relationship between the graduate profile and the competences of the curriculum courses of the secondary school professional school of the National University of Puno Altiplano, in the 2016 period. The research focus was quantitative of applied type. The design is non-experimental, transversal, descriptive and correlational. The study population consists of 60 subjects. The technique used was observation and the observation card instrument. The results indicate that there is a considerable positive correlation (0.830) which indicates that there is a significant relationship between the graduate profile and the competences proposed in the subjects of the flexible curriculum by competencies of the Secondary School Vocational School of the National University of the Puno Highlands.
Keywords: Graduate profile; competencies; curriculum; university